Pengelolaan Pelaksanaan Bimbingan dan Konseling di SDN 1 Kekeri - Witono, A. Hari; Widiada, I Ketut; Saputra, Heri Hadi; Khair, Baiq Niswatul; Rosyidah, Awal N. K.; Setiawan, Heri (Magister Pendidikan Dasar FKIP Universitas Mataram, 2024)
This research is aimed at finding out the pattern of management and implementation of BK at SDN 1 Kekeri, Kec. Gunungsari. The method used in this research is a qualitative method, with a descriptive research approach where data is collected and expressed in the form of words and images, the words are arranged in sentences, for example sentences resulting from interviews between researchers and informants. This research will be carried out at SDN Kekeri District. Gunungsari, Kab. West Lombok and is planned to be implemented for 8 months. The research subjects were school principals, teachers and students. Primary data sources, which include data in the form of interviews obtained from school principals, teachers and students. Apart from interviews, researchers also use data sources in the form of field observations, namely in the form of classroom learning processes and documentation. Secondary data is data sourced from reports or related documents found at the research location. This research uses data collection techniques: in-depth interviews, observation, and documentation. Data analysis uses the Miles, Huberman and Saldana model of data analysis with stages: data condensation, data display, and conclusion drawing/verifications. Based on the research results, several important points were obtained. At SDN 1 Kekeri, various supports and assistance are provided by class teachers as supervisors/counselors at the elementary school. Various types of guidance and counseling support services and activities are carried out by class teachers with the aim of solving and overcoming potential problems arising in students. The scope of management and implementation of BK at SDN 1 Kekekri includes: (1) Direct services; (2) guidance and counseling services through the media; (3) administrative activities; and (4) additional duties/professional development for guidance and counseling teachers or counselors. To ensure the proper implementation of BK services at SDN 1 Kekeri, supervision of guidance is needed both technically and administratively. Supervision duties at schools are carried out by the school principal, deputy principal, and supervisors from the District education office. West Lombok